Copy Number Variations and Cognitive Phenotypes in Unselected Populations. Issue 9 (September 2015) - Männik, Katrin; Mägi, Reedik; Macé, Aurélien; Cole, Ben; Guyatt, Anna L.; Shihab, Hashem A.; Maillard, Anne M.; Alavere, Helene; Kolk, Anneli; Reigo, Anu; Mihailov, Evelin; Leitsalu, Liis; et al.
<x xml:space="preserve">Abstract</x> ABSTRACT In the human genome, genetic sequences that differ in the numbers of copies, or so-called copy number variations (CNVs), can be associated with intellectual disability and developmental delay. Large, recurrent CNVs are particularly associated with these complex disorders. Previous studies of the effects of large CNVs have generally pediatric subjects with clinical disordered, and there are more limited data on the population frequency in asymptomatic adults. This study looks at the adult carriers of CNVs and aims to assess the consequences of rare CNVs. The study utilized the Estonian Genome Center at the University of Tartu, which includes 52, 000 participants. For CV analysis, genomic DNA from 6819 individuals was used for the discovery cohort and 1058 for the replication cohorts. The phenotypes of CNV carriers were compared with phenotypes in the general population. A third "high-functioning replication cohort" of 933, as well as a UK cohort of 5218, a US cohort of 2390, and an Italian cohort of 451, was used for replication for further analysis regarding education attainment. In the Estonian cohort, 56 of 7877 participants were identified as carriers of known autosomal genomic disorders. Of the 6819 individuals in the discovery cohort, 509 were identified as duplication carriers, and 216 were identified as deletion carriers. Of the 216 deletion carriers of at least 250 kb, 11 (5.1%) had an intellectual disability (odds ratio [OR], 3.16%; 95% confidence interval [CI], 1.51–5.98; P = 1.5E−03). Of 102 carrier with a duplication of at least 1 Mb, 6 (5.9%) had an intellectual disability (OR, 3.67; 95% CI, 1.29–8.54; P = 0.008). This was compared with 114 in the Estonian cohort of 6819 (1.7%); 3.2% of rare CNV carriers were diagnosed with intellectual disabilities, whereas 1.7% of the Estonian cohort was diagnosed with intellectual disability (OR, 1.93; 95% CI, 1.17–3.06; P = 0.007). Larger CNV size was shown to be associated with frequency of intellectual disability; 33.5% of deletion carriers (OR, 1.48; 95% CI, 1.12–1.95; P = 0.005) and 39.1% of duplication carriers (OR; 1.89; 95% CI, 1.27–2.8; P = 1.6e−03) did not graduate from high school. Evidence supporting an association between prevalence of intellectual disability and carrier status was found. Analysis of the Italian, United States, and United Kingdom cohorts supported the association between rare CNVs and lower educational attainment, but further replication of the study's findings is needed.